Congenital Glaucoma: a Novel Ocular Manifestation of Hajdu-Cheney Syndrome. (21st October 2018) - Swan, L.; Gole, G.; Sabesan, V.; Cardinal, J.; Coman, D.
Abstract : Hajdu-Cheney Syndrome (HSC) is a rare multisystem disease in which the phenotype involves acro-osteolysis, severe osteoporosis, short stature, wormian bones, facial dysmorphism, central neurological abnormalities, cardiovascular defects, and polycystic kidneys. We describe an infant with severe manifestations of HCS in whom congenital glaucoma was a significant early feature, which has not been reported to date. HCS cases reported to date have involved truncating mutations in exon 34 of NOTCH2 upstream the PEST domain that lead to the development of a truncated and stable NOTCH2 protein which upregluates notch signaling. We describe a hitherto undescribed missense mutation that is predicted to be pathogenic, with functional characterization remaining to be performed. Serpentine fibula-polycystic kidney syndrome (SFPKS) is allelic to HCS and commonly associated with missense NOTCH2 mutations. Our patient provides new ophthalmological manifestations of HCS and provides insight into the potential role of notch signaling in the anterior chamber development.